2012
DOI: 10.1007/s10815-012-9856-1
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptins in human reproduction—future therapeutic potential

Abstract: Kps have proven as pivotal regulators of the reproduction, with the ability to integrate signals from both internal and external sources. Knowledge about signaling mechanisms involved in Kp stimulation of GnRH and with human studies has made it possible that therapeutically available Kp agonists/antagonists may be used for treatment of delayed puberty/HH, Hypothalamic amenorrhea and in prevention of spread of malignant ovarian/gonadal malignancies along with uses in some eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 134 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…On detailed analysis of families having knowledge ,it was demonstrated that in cases of normosmic HH, which is a monogenic mendelian disease there is an involvement of 6 genes namely GnRH1 [36,37], Gn RH R [26,38-,39], KISS1R [40][41], KISS1 [42,43] reviewed in kkk] TAC3 and its receptor TAC3R [44,]. Animal model studies have given a better understanding regarding the role of these factors in the gonadotropic axis [33,44].…”
Section: Hypogonadotropic Hypogonadismmentioning
confidence: 99%
See 1 more Smart Citation
“…On detailed analysis of families having knowledge ,it was demonstrated that in cases of normosmic HH, which is a monogenic mendelian disease there is an involvement of 6 genes namely GnRH1 [36,37], Gn RH R [26,38-,39], KISS1R [40][41], KISS1 [42,43] reviewed in kkk] TAC3 and its receptor TAC3R [44,]. Animal model studies have given a better understanding regarding the role of these factors in the gonadotropic axis [33,44].…”
Section: Hypogonadotropic Hypogonadismmentioning
confidence: 99%
“…Since this is costly all patients might not afford it [83,84]. Recently Kp agonists have been tried in some cases having KISS1/KISS1R mutations [43,85] although not available in every country. Although NKB is not effective it being downstream of KISS, KP agonists are also effective in TAC3/TAC3R mutations [86][87][88].…”
Section: Fertility Treatmentmentioning
confidence: 99%
“…This peptide can get further hydrolyzed into a number of truncated fragments; kisspeptin 54(Kp54/metastin with 54 amino acids), kisspeptin 14(14 amino acids) and Kp13 and Kp10 with 13and 10 amino acids respectively. 1,2 Initially kisspeptin 54 got named metastin since it was isolated in metastatic tissues though both are synonymous fragments encoded by the same gene that encodes the larger peptide which then further gets broken into smaller fragments by enzymes. Then Jayasena et al 3 started studying them in human reproduction…”
Section: Commentarymentioning
confidence: 99%
“…Further since Kp 10 is a potent stimulator of LH and increases pulse frequency in men and thereby LH and testosterone levels in normal men there may be a potential role of Kp agonists in HH due to KISS 1/KISS1R mutations ( [129], reviewed in [130]).…”
Section: Role Of Estradiol (In Male Chh)mentioning
confidence: 99%